Success Level of Nile Nile Fish (Oreochromis Niloticus) Cultivation In Supporting Food Security In Sukaraya Village, Bekasi Regency - Inayah Fitriana; Mohamad Sam'un; Ali Fahmi Syahputra (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the success level of Nile tilapia (Oreochromis niloticus) farming in supporting food security in Sukaraya Village, Bekasi Regency, identify factors influencing farming success, and examine its contribution to community food security. A qualitative method with a case study approach was employed. Data were collected through observation, interviews, documentation, and questionnaires involving village officials, program facilitators, relevant institutions, and 15 beneficiary Nile tilapia farmers participating in the village food security program. The success level of farming was assessed based on the implementation of Good Fish Rearing Practices (CPIB), farming productivity, and actual production achievement compared to the established production targets. The contribution to food security was analyzed through the dimensions of food availability, accessibility, and utilization. The results indicate that CPIB principles were generally implemented well in terms of farming facility preparation, seed selection, feeding practices, fish health management, harvesting, and post-harvest handling. However, farming productivity was constrained by suboptimal feed management, unstable water quality, and relatively high fish mortality rates in several ponds. Based on the production evaluation of 15 farmers, 3 were categorized as successful, 5 as unsuccessful, and 7 as failed. These findings suggest that farming success remains varied and is strongly influenced by farmers’ technical capacity to apply proper aquaculture practices. Nevertheless, Nile tilapia farming contributes to food security by increasing the availability of animal protein sources, improving access to nutritious food, and supporting household food consumption. Therefore, strengthening farmers’ capacity, providing continuous technical assistance, and implementing intensive monitoring are necessary to enhance productivity and ensure the sustainability of the program.